Brexit had no measurable effect on Irish exporters - Benjamin Elsner; Eoin T. Flaherty; Stefanie Haller (University College Dublin, UCD School of Economics, 2024)
We study the impact of the Brexit referendum on Irish exporters to the UK. The referendum triggered a sharp devaluation of the British pound vis-a-vis the euro and led to considerable uncertainty about future trade relations between the UK and the EU. Using administrative data on the universe of Irish exporters, we compare exporters with different levels of exposure to the UK market before the referendum. Our findings do not point to a significant effect of the referendum on Irish exporters. Over the period 2015-2021, the firms least exposed to the UK - but most internationalised otherwise - had considerably higher exit rates from exporting to the UK and from the market overall. They also saw greater declines in employment and sales compared to more exposed firms. We do not find significant differences for export volumes to the UK or elsewhere or for average wages. These findings are robust to controlling for a variety of firm characteristics.
Keywords: E65; F02; F13; F14; F15; F16; F31; F40; 330; Brexit; firm performance; Trade; Wages; Employment